Coastal Analyst System from Space Imagery Engine (CASSIE): Shoreline management module. (June 2021) - Almeida, Luis Pedro; Efraim de Oliveira, Israel; Lyra, Rodrigo; Scaranto Dazzi, Rudimar Luís; Martins, Vinícius Gabriel; Henrique da Fontoura Klein, Antonio
Abstract: CASSIE is an open-source web tool for automatic shoreline mapping and analysis using satellite imagery (www.cassiengine.com ). This tool was built in JavaScript, using Google Earth Engine (GEE) API, and can be applied to any coastal region on Earth where a boundary between water and land exists. CASSIE use the Landsat and Sentinel-2 satellite imagery, freely available from GEE, and implements an automatic shoreline detection using the normalized difference water index (NDWI) together with Otsu image segmentation algorithm. The satellite-derived shorelines are analysed for a set of user-defined cross-shore transects along which several statistical analyses are performed. Comparisons of the CASSIE-derived shorelines and rate of changes with state-of-the art methods show that the products from this tool have sub-pixel accuracy. The new concept of big-data cloud-based computing and storage platform (GEE), together with a user-friendly interface and high level of automation makes of CASSIE a complete tool to support a wide variety of studies and applications where the knowledge of the shoreline behaviour is fundamental. Highlights: CASSIE: new web tool for automatic shoreline detection and analysis from satellite imagery. Open-source, and built with JavaScript using Google Earth Engine API. CASSIE enables access to Sentinel-2 and Landsat satellite imagery datasets. The accuracy of the CASSIE-derived shoreline and rates-of-changes are sub-pixel. Can be applied at any coastal region and requires minimum computer memory and storage.